IMPLEMENTASI PENDIDIKAN BERBASIS BUDAYA LOKAL PADA PEMBELAJARAN IPS DI KELAS VIIIA SMPN 1 SEMITAU KECAMATAN SEMITAU KABUPATEN KAPUAS HULU - Indrawan, Fernando Ario; Buwono, Sri; Wiyono, Hadi; Barella, Yusawinur; Fitriana, Dina (Prodi Pendidikan IPS, Universitas Tanjungpura, 2025)
The purpose of this research is to examine the planning, implementation, and challenges in the application of local culture-based education in Social Studies (IPS) learning in Class VIII.A of SMP N 1 Semitau, Kapuas Hulu Regency. This study was conducted using a qualitative research method, with data collection techniques including observation at school, interviews, and documentation carried out with Social Studies teachers and the curriculum coordinator of SMPN 1 Semitau as sources or informants. Data reduction was performed by eliminating irrelevant data and including data relevant to the research focus. The results show that the planning and integration of local culture into learning is carried out by designing learning activities and implementing them through classroom discussions, local culture simulations, and extracurricular activities. However, there are several challenges in its implementation, including a lack of specific teaching materials and curriculum, as well as students' diverse levels of understanding